ANALISIS KELAYAKAN FINANSIAL USAHATANI KOPI DI KABUPATEN LAMPUNG BARAT (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2022)
The purpose of this study was to financially analyze coffee farming in West Lampung Regency. This research was conducted in Way Tenong District, from September to October 2020 using a survey method. The sample in this study was 77 respondents who were selected at simple random sampling. Data were analyzed using quantitative descriptive analysis with financial feasibility analysis, namely five eligibility criteria, namely Gross B/C Ratio, Net B/C Ratio, NVP, IRR, and PP as well as sensitivity analysis. The results showed that financially coffee farming in West Lampung Regency. Sensitivity analysis with the assumption of an increase in production costs of 2.03 percent and a decrease in production of 4.00 percent resulted that the eligibility criteria for Internal Rate of Return (IRR), Gross B/C, and Net B/C is sensitive to changes.